Green Insight of High Performance UTGE Operation in Nano-Sensitive Electro-Analysis of Meropenem by Adsorptive Stripping Voltammetry. Issue 14 (1st January 2018) - Fayed, Ahmed S.; Youssif, Rania M.; Hendawy, Hassan A. M.; Salama, Nahla N.; Elzanfaly, Eman S.
Abstract : The present study concerns with investigation of the electrochemical activity of meropenem (MP) at ultra-trace graphite electrode (UTGE). The electrochemical measurements were performed in various buffer solutions in pH range (2.0–8.0). One irreversible anodic peak was observed in acidic medium. The effects of pH and scan rate on the peak current and potential were studied. The adsorption-controlled nature of MP peak was demonstrated. Therefore, it is directed to develop adsorptive stripping square wave voltammetric technique (AdS-SWV) for quantitative determination of MP in drug substance, pharmaceutical vials and in presence of interference substances. Under optimum experimental conditions, a linear dependence relationship was obtained over MP concentration range of 500.0–15000.0 nM. The limits of detection (LOD) and quantification (LOQ) were 160.0 and 470.0 nM respectively. Chemical safety is assessed at different aspects. Qualitative and quantitative metrics reveal excellent eco-friendly voltammetric method. In spite of high budget of UTGE; multiple merits of nano-sensitivity, selectivity, greenness evidence and high efficiency encourage wide application of our developed method in QC using UTGE in comparison to other chemically-modified electrodes.